Penundaan Pembayaran Pajak Bea Perolehan Hak atas Tanah dan Bangunan dalam Program PTSL; Sebuah Analisis Hukum - Radja Haehta Sembada; Iqbal Taufik Maulana; Adi Permadi; Deden Faldi Ramadan (IAIN Langsa, 2026)
This study aims to analyze the legal consequences of land title certificates that still bear unpaid BPHTB (Duty on the Acquisition of Land and Building Rights) tax liabilities within the implementation context of the Complete Systematic Land Registration Program (PTSL), as well as to identify the challenges faced by the Regional Revenue Agency (Bapenda) in collecting outstanding BPHTB. This research falls under the category of qualitative library research with a normative legal study approach. Primary sources include statutory regulations such as Law No. 28 of 2009 on Regional Taxes, Law No. 5 of 1960 on Basic Agrarian Principles (UUPA), and Ministerial Regulation of ATR/BPN No. 6 of 2018. The study concludes that the legally permitted postponement of BPHTB payments through regional head discretion has led to implementation conflicts with administrative land regulations—particularly regarding the issuance of land certificates by the National Land Agency (BPN), which requires proof of BPHTB payment. As a result, certificates issued under tax-deferred status do not carry full legal force for use as collateral or for land transactions. The regulatory disharmony between local fiscal policies and national administrative requirements has created legal uncertainty for the public, especially low-income groups who are the primary target of the PTSL program.